Mental health literacy among Arab university students in Israel: A qualitative study. (November 2022) - Khatib, Anwar; Abo-Rass, Fareeda
Background: There has been a noticeable increase in the number of studies concerned with mental health literacy (MHL), specifically among students. Still, very few studies have examined MHL among students of non-Western minority groups. Aims: This study examined MHL among Arab students in Israel based on Jorm's conceptual framework. Methods: Twenty-eight Arab students in Israel took part in semi-structured, in-depth interviews. Most were single and Muslim, in their second year of studies, and most reported low socioeconomic status. The data were analyzed thematically, guided by the Jorm's six MHL dimensions. Results: Different levels of literacy were found in the various MHL dimensions. The participants identified severe mental disorders more easily than mood disorders; reported a variety of possible causes of mental disorders; were well aware of available professional help (apart for rehabilitative services); identified significant barriers to mental health help seeking, as Arabs; and reported the internet as a major source of information about mental health problems and their treatment Conclusions: The participants' MHL appeared to be associated with their unique sociocultural characteristics. This study stresses the need to raise MHL among Arab students in Israel, and in particular to promote positive attitudes to seeking professional help. It also highlights the need to develop culturally adapted mental health interventions for the Arab population in Israel.